Pengembangan bahan ajar saintifik berbantuan scratch pada materi segiempat dan segitiga - Elna Nurhasanah; Martin Bernard; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to analyze the feasibility and practicality of scientific teaching materials assisted by scratch. This development research was conducted using the 4D method which was limited to the third step including the define, design, and development stages. At the feasibility and practicality test data analysis stage, data were collected through observation, questionnaires, and documentation. The feasibility of teaching materials is analyzed based on the results of expert validation and the practicality of teaching materials based on the results of student answers.Â  The results of this study indicate that the teaching materials tested are feasible and practical as learning materials for students. This is based on the results of validation by experts on the practicality of teaching materials filled in by students. The results of expert validation resulted in an average score of 91.83% with a very valid category, which can be said to be suitable for use in the field. The results of the practicality questionnaire analysis show that teaching materials are considered practical by students with a percentage of 85% on a small scale and 87% on a wide scale with a very practical category. This can show that the scientific teaching materials for quadrilateral and triangle materials assisted by scratch are very good for use during the math learning process.